2019
DOI: 10.1016/j.xphs.2018.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ARA/PPI Drug-Drug Interactions at the Drug Discovery and Development Interface

Abstract: Advances in understanding of human disease have prompted the U.S. Food and Drug Administration to classify certain molecules as "break-through therapies," providing an accelerated review that may potentially enhance the quality of patient lives. With this designation come compressed timelines to develop drug products, which are not only suitable for clinic trials but can also be approved and brought to the market rapidly. Early risk identification for decreased oral absorption due to drug-drug interactions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…The precise impact of the observed fluid volume changes, in combination with the PPI-induced drop in gastric pH, on the absorption of ritonavir will be further evaluated using in vitro dissolution testing in combination with physiologically-based pharmacokinetic (PBPK) modelling. PBPK modelling has previously been utilized to predict in vivo drug-drug interactions between weakly basic compounds and PPIs or other acid-reducing agents [ 31 , 32 , 33 ]. From a broader perspective, the results of this study should be taken into consideration when developing and testing new drug candidates especially for populations in which PPI use is most frequent, including elderly [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The precise impact of the observed fluid volume changes, in combination with the PPI-induced drop in gastric pH, on the absorption of ritonavir will be further evaluated using in vitro dissolution testing in combination with physiologically-based pharmacokinetic (PBPK) modelling. PBPK modelling has previously been utilized to predict in vivo drug-drug interactions between weakly basic compounds and PPIs or other acid-reducing agents [ 31 , 32 , 33 ]. From a broader perspective, the results of this study should be taken into consideration when developing and testing new drug candidates especially for populations in which PPI use is most frequent, including elderly [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Publication bias and case-by-case parameter fitting reduce the reliability of the prediction model [ 19 ]. Recently, a commercial software product was systematically evaluated regarding ARA DDI prediction for weak base drugs [ 20 ]. The results suggest that scientific knowledge in this area is still premature (Figures 4 and 5 in [ 20 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a commercial software product was systematically evaluated regarding ARA DDI prediction for weak base drugs [ 20 ]. The results suggest that scientific knowledge in this area is still premature (Figures 4 and 5 in [ 20 ]). In that study, free and salt forms were not differentiated as drug substances.…”
Section: Introductionmentioning
confidence: 99%
“…20 Recently, a study suggested that the PBPK model that was developed at the preclinical stage could correctly identify pH-dependent DDI potential for 78% drugs although false negative prediction was observed. 21 However, there is still limited application of PBPK modeling to address the questions related to absorption-related DDIs at the stage of regulatory submissions. [22][23][24][25] In the years of 2013-2017, PBPK modeling has been used in two New Drug Application submissions to predict the liability of pH-dependent DDIs to support the labeling recommendations.…”
Section: Discussionmentioning
confidence: 99%